Treadmill associated head injuries on the rise: an 18 year review of U.S. emergency room visits. (12th May 2018) - Catapano, Joshua S.; Chapman, Alistair J.; Farber, S. Harrison; Horner, Lance P.; Morgan, Clinton; Brigeman, Scott; Hendricks, Benjamin K.; Lu, Minggen; Fraser, Douglas R.
ABSTRACT: Objective : The treadmill is the most commonly used aerobic exercise equipment with studies showing many gym-related injuries are attributed to treadmills. The purpose of this study is to examine the incidence of treadmill-associated head injuries within the US. Methods : Retrospective data from 1997 to 2014 was collected via the National Electronic Injury Surveillance System, which provides annual es7timates of injuries associated with consumer products. Patients over 18 years who sustained treadmill-associated head injuries were included, and the estimated annual incidence was determined. Results : An estimated 4929 patients presented to US emergency departments with a head injury while exercising on a treadmill between 1997 and 2014. A >1000% increase in the number of head injuries was observed over the study period ( p -value <0.001). Patients over 50 had a 14 times greater risk of admission than younger patients ( p -value <0.001). Injuries were greater in women than men. Conclusion : Our study demonstrates a significant increase treadmill-associated head injuries from 1997 to 2014. This phenomenon is most pronounced in older and female populations. The exact etiology of this large increase remains unclear. Education on the proper use of treadmills as well as further investigation into the cause of the increase are warranted.